From radical labels to moderate Islam: the transformation of the Salafism movement in Indonesia - Tabroni, Roni; Idham, Idham (IAIN Salatiga, 2023)
The contemporary Salafist movement in Indonesia began to develop in the1970s. In its development, the Salafist movement later gave rise to variousfactions. One of the results of the dynamic and contestation of these variousfactions was the emergence of religious moderation movements of Salafists.This article tries to explain the role of The Islamic Propagation Council ofIndonesia (DDII) and the Institute for the Study of Islam and Arabic (LIPIA) inthe dynamics of the Salafist movement and to trace and describe the dynamicsand the religious moderation movements of the Salafist groups, particularly inJakarta, Indonesia. The research methods used are historical research methodsand qualitative methods with a case study approach. The results show that thereare adaptations emerging from the contemporary Salafist movement.These adaptations can be seen in the acceptance of the concept of the unitary stateof the Republic of Indonesia and democracy even within the framework ofSharia and the presence of moderation or anti-violence ideas. This shows theflexibility of the movement which arises from the need for the sustainability ofthe organization or movement. In addition, cities present different challenges.This then requires an organization to adapt, either in terms of strategy, method,or proselytizing approach.